The influence of cross-generation attitude on halal food products - Zuraini M.I; Muhammad Afiq M.; Nurzulain Z. (Penerbit Universiti Kebangsaan Malaysia, 2019)
The term ‘halal’ has been used as a tool by most food industries to attain competitive advantage. Nevertheless, the increase in demand for halal food products may be stunted due to the lack of awareness from the consumers, especially the younger generation. Young consumers may take halal issues lightly. Therefore, this study was conducted to identify the influence of cross-generation (namely Generation X, Y and Z) attitude on halal food products. Data were collected from 410 respondents in Shah Alam, Selangor, Malaysia through an online survey. The data were analysed using SPSS for descriptive statistics and one-way ANOVA. The results indicated variances in cross-generation attitude towards halal food products. The study outcomes are beneficial for manufacturers in producing halal food products based on their intended group of consumers. Further study should look into determining the factors that may influence cross-generation attitudes on halal food products.